2003
DOI: 10.1007/s00439-003-1012-7
|View full text |Cite
|
Sign up to set email alerts
|

Increased risk for developmental delay in Saethre-Chotzen syndrome is associated with TWIST deletions: an improved strategy for TWIST mutation screening

Abstract: The majority of patients with Saethre-Chotzen syndrome have mutations in the TWIST gene, which codes for a basic helix-loop-helix transcription factor. Of the genetic alterations identified in TWIST, nonsense mutations, frameshifts secondary to small deletions or insertions, and large deletions implicate haploinsufficiency as the pathogenic mechanism. We identified three novel intragenic mutations and six deletions in our patients by using a new strategy to screen for TWIST mutations. We used polymerase chain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
1
3

Year Published

2005
2005
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(51 citation statements)
references
References 35 publications
(42 reference statements)
1
46
1
3
Order By: Relevance
“…32 With respect to mental performance, carriers of TWIST mutations in the present series did not differ from the average population. 20 Contrary to other authors, 33,34 we found that even deletions of the entire TWIST gene did not adversely affect cognitive function in our SCS patients. Compared to three deletion cases reported by Johnson et al, 33 the size of the deletions in our patients appears to be smaller, particularly in the 3 0 -direction (Table 3), but further analysis is necessary.…”
Section: Discussioncontrasting
confidence: 61%
“…32 With respect to mental performance, carriers of TWIST mutations in the present series did not differ from the average population. 20 Contrary to other authors, 33,34 we found that even deletions of the entire TWIST gene did not adversely affect cognitive function in our SCS patients. Compared to three deletion cases reported by Johnson et al, 33 the size of the deletions in our patients appears to be smaller, particularly in the 3 0 -direction (Table 3), but further analysis is necessary.…”
Section: Discussioncontrasting
confidence: 61%
“…As these possibilities were fully excluded, the search for the cis regulatory mutation that causes QPD must now extend beyond PLAU to identify the unique sequence changes that markedly increase transcription of the linked PLAU allele during megakaryocyte differentiation. In some disorders, the causative mutation that alters transcription is quite far (5Ј and 3Ј) from the dysregulated gene, 13,14 and it can be in an unrelated, neighboring gene. 15,16 Regulatory elements with cis or trans effects have been identified as far as 1 Mb away from the genes transcribed.…”
Section: Resultsmentioning
confidence: 99%
“…The duplication is located right downstream of the NSD1 gene, a region which appears critical for the expression of the gene, and regulatory elements might be disrupted or the expression of a not amplified critical gene might be otherwise affected by the duplicated region [Kasnauskiene et al, 2011]. Other position-effect genes have been reported in which functions were disturbed by breakpoints of 125 kb, 260 kb, or 120 kb downstream of the critical genes in cases of aniridia [Kleinjan et al, 2001], Saethre-Chotzen syndrome [Cai et al, 2007], and lymphedema distichiasis [Fang et al, 2000], respectively. Gene function disturbance by the second mechanism could be associated with the inappropriate spreading of repressive (or active) chromatin across a gene locus by juxtaposition next to specific sequences (e.g.…”
Section: Discussionmentioning
confidence: 99%